Paper-based analytical devices for smart foodborne pathogen detection - Hadeer M. Bedair; Mohamed Emara; Tamer M. Samir; Mahmoud A.F. Khalil; Shima Mahmoud Ali; Mahmoud Hamed; Fotouh R. Mansour (Talanta Open)
Food safety continues to be a critical global challenge, with foodborne pathogens posing significant risks to public health and economic stability. The rapid detection of these pathogens, especially in resource-limited settings, is essential to mitigate outbreaks and enhance food safety systems. This review explores the advancements in paper-based analytical devices (PADs) as a practical, cost-effective, and portable solution for the detection of foodborne pathogens. Various detection platforms, including nucleic acid-based sensors, aptamer-integrated systems, Immunochromatographic assays, and nanoparticle-enhanced biosensors, are evaluated for their effectiveness in rapid and on-site testing. PADs meet the key requirements for point-of-need testing, including simplicity, speed, affordability, and versatility. Their ability to integrate with modern technologies such as smartphones and machine learning enhances their analytical performance and accessibility. Despite their promise, challenges remain, including sensitivity limitations and scalability. Addressing these gaps could unlock the full potential of PADs for widespread use in food safety monitoring and pathogen detection.